Flexibility & structure: Community engagement on climate action & large infrastructure delivery. (August 2022) - Boyle, Evan; Galvin, Martin; Revez, Alexandra; Deane, Aoife; Ó Gallachóir, Brian; Mullally, Gerard
Abstract: This research paper explores the role of citizen and community engagement in climate mitigation projects, particularly related to climate infrastructure development in the Irish context. A change is needed with relation to the way in which institutions interact with community groups and citizens in order to effectively go about implementing the necessary measures to expedite the transition to a low-carbon energy system. Within this research we implement a co-production approach to the investigation of community engagement practices within public bodies, moving from framings centred on social acceptance towards social acceptability. The 2020 OECD report stressed the importance of co-production in transdisciplinary approaches to sustainable development, climate action and the Sustainable Development Goals. We develop a range of good practice guidelines for community engagement that seek to connect, build and improve current mitigation measures and on from this suggest policy measures for their implementation. The paper sets the foundations for developing a co-production framework for climate related infrastructure developments between citizens, communities and public bodies. Highlights: Community engagement on infrastructure is crucial for future decarbonisation targets. A structured good practice approach to C.E. should be implemented cross-institutionally. Personal characteristics play a role in good engagement practices. Flexibility is needed to respond to different community contexts.